Learning among Equals and Cooperative Learning: Psychopedagogical Principles and Teaching Methods - Sánchez Chacón, Giovanni (2015)
This article shows a literature review about the theoretical fundamentals, structures of social organization and dimensions of peer learning, which will be then related to cooperative learning concepts and the conditions for its implementation in the classroom through the main methods identified in the specialized literature.